Results of unicompartmental osteoarthritis knee treated with high tibial osteotomy: a case series - Tahbildar, Pranjal; B. S., Shabeer; Sonowal, Kiran; Sarkar, Imdadur Rahman (International Journal of Research in Orthopaedics, 2023)
High tibial osteotomy (HTO) being a re-emerged common procedure in orthopaedic practice now, which is safe and relatively simple and cost-effective technique requiring careful selection of subjects and precision of technique. Background: In isolated medial unicompartmental osteoarthritis (OA) of knee, in a physiologically young and high demanding individual, where preservation of knee is required, unicompartmental knee arthroplasty and total knee arthroplasty are not considered as treatment options. HTO is an excellent treatment option where the requirement of technical skills and infrastructure are less and high-volume low-cost surgeries can be performed with minimum instrumentation. 20 selected patients with unicompartmental OA of knee who attended the OPD of orthopaedics, Jorhat Medical College and Hospital were the subjects of this study, during the period of study from June 2020 to May 2021. In our study, average age was 55.9 years; higher incidence among females; higher incidence of OA in left knee; 80% of cases presented at Kellgren and Lawrence grade 2 and 3; most of the cases were having BMI within normal range and varus deformity of knee; plate and screw fixation after HTO provides more rigid fixation than staples alone. In this study, we got 60% good and 30% fair results after 6 months to 1 year of follow-up. Successful HTO is a very effective alternative low-cost surgery that makes it possible to delay or avoid knee arthroplasty in well selected patients.